2011
DOI: 10.1007/s11224-011-9745-8
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and computational studies on (Z)-1-((4-phenylamino)phenylamino)-methylene)naphthalen-2(1H)-one

Abstract: The Schiff base compound (Z)-1-((4-phenylamino)phenylamino)methylene)naphthalen-2(1H)-one has been synthesized and characterized by IR, UV-Vis, and X-ray single-crystal determination. Molecular geometry from X-ray experiment of the title compound in the ground state have been compared using the Hartree-Fock (HF) and density functional method (B3LYP) with 6-31G(d,p) basis set. Calculated results show that density functional theory DFT and HF can well reproduce the structure of the title compound. Using the time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…In general, o-hydroxy Schiff bases display two possible tautomeric forms, the enol-imine (OH) and the keto-amine (NH) forms (see Figure 1). Depending on the tautomers, two types of intramolecular hydrogen bonds are observed in Schiff bases: O-H···N in enol-imine [19,20] and N-H···O in keto-amine [21][22][23] tautomers. Different methods were used to show the presence of the enol-imine and keto-amine forms, among them UV-Vis, IR, 1 H, 13 C * Email: hasantanak@amasya.edu.tr NMR spectroscopy and X-ray crystallography techniques [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…In general, o-hydroxy Schiff bases display two possible tautomeric forms, the enol-imine (OH) and the keto-amine (NH) forms (see Figure 1). Depending on the tautomers, two types of intramolecular hydrogen bonds are observed in Schiff bases: O-H···N in enol-imine [19,20] and N-H···O in keto-amine [21][22][23] tautomers. Different methods were used to show the presence of the enol-imine and keto-amine forms, among them UV-Vis, IR, 1 H, 13 C * Email: hasantanak@amasya.edu.tr NMR spectroscopy and X-ray crystallography techniques [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…However, new absorption band for the 1, 2 and 3 compounds at 431, 436 and 398 (~400) nm respectively arising from π-π* transition belongs to the keto form of o-hydroxy Schiff bases [34]. The keto form is more polar than enol form; thus easily stabilized by polar solvents as DMF.…”
Section: Electronic Absorption Spectramentioning
confidence: 99%
“…The tautomerism of Schiff bases has been studied by (Alpaslan et al, 2011;Blagus et al, 2010;Ünver et al, 2002). It demonstrated that the stabilization of the Keto-amino tautomer in the crystal depend mostly on the parent o-hydroxyl aldehyde, the type of the N-substituent, the electron withdrawing or donating of the N-substituent, their position and stereo chemistry (Blagus et al, 2010).…”
Section: S1 Commentmentioning
confidence: 99%